2009
DOI: 10.1016/j.drugalcdep.2009.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Pathways between nonmedical opioid use/dependence and psychiatric disorders: Results from the National Epidemiologic Survey on Alcohol and Related Conditions

Abstract: Background-While nonmedical use of opioids and psychiatric disorders are prevalent in the population, little is known about the temporal ordering between nonmedical opioid use and dependence and psychiatric disorders.Method-Data were gathered in a face-to-face survey of the United States conducted in the 2001-2002 (NESARC wave 1). Participants were household and group quarters residents aged 18 years and older (n=43,093). Cox proportional hazards models with time-dependent covariates were used to investigate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 61 publications
10
114
3
Order By: Relevance
“…32,59,60 Multiple etiologies likely account for the comorbidities, and further research is required to elucidate the role of different causal directionalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,59,60 Multiple etiologies likely account for the comorbidities, and further research is required to elucidate the role of different causal directionalities.…”
Section: Discussionmentioning
confidence: 99%
“…The Huang et al 31 analysis of the US NESARC demonstrated that NMPOU was positively associated with mood disorders, anxiety disorders, and personality disorders. The Martins et al 32 analysis of the same data demonstrated that preexisting mood disorders and anxiety disorders increased the likelihood of NMPOU. Conversely, the Novak et al 33 analysis demonstrated that mood and antisocial personality disorders increased the likelihood of disordered NMPOU, and anxiety disorder increased the likelihood of nondisordered NMPOU, compared with no disorder.…”
Section: Nmpou and Mental Health Problemsmentioning
confidence: 93%
“…Given the extent of the problem, many studies have characterized individuals who use nonmedical prescription opioids to better understand the population of nonmedical prescription opioid users (Becker et al, 2008;Brands et al, 2004;Huang et al, 2006;Martins et al, 2009b;Sigmon, 2006). A strong association between psychiatric disorders and nonmedical prescription opioid use (Becker et al, 2008;Cicero et al, 2008) and disorders (Grella et al, 2009;Huang et al, 2006;Martins et al, 2009a) suggests the importance of addressing mental health problems among this population. A high risk for mental disorders motivates examination of risk for suicidal behavior (ideation and/or attempt), as mental disorders are among the strongest risk factors for suicidal ideation (Goldney et al, 2000).…”
Section: T He Increase Of Nonmedical Prescription Opioid Use In the Umentioning
confidence: 99%
“…Although the health, economic, and social consequences of the prescription opioid epidemic are broad,7, 8 people with mental illness and non‐opioid addictions show disproportionate risk of suffering serious complications of increased access to prescription opioids 9, 10, 11, 12. Pre‐existing mental illness is major risk factor for acquisition of opioid use disorders, and non‐medical opioid use that escalates to addiction is a risk factor for onset of mental illness 13. Whether produced by “Adverse Selection” where doctors are more likely to prescribe high risk opioid regimens to high risk (eg, mentally ill/addicted) patients,14, 15 or biological vulnerability to addictions in mentally ill brains,16, 17 strong linkages between mental illness and opioid addictions indicate the need to recognize and treat prescription opioid addictions in behavioral health settings.…”
Section: Introductionmentioning
confidence: 99%